2000
DOI: 10.1159/000017494
|View full text |Cite
|
Sign up to set email alerts
|

Psychosomatics and Dermatology: Comparison between Objective Data and Subjective Impressions Given by Patients and Dermatologists

Abstract: The authors wanted to assess the psychological part in the etiology of different skin diseases in adult outpatients in a dermatological university clinic. The other aim of this study was to explore the dermatologist’s perception of a psychological involvement in the etiology of some skin diseases. This was compared with the patients’ perception of it and with objective data obtained by self-rating questionnaires. 554 outpatients consulting for psoriasis, alopecia areata, eczema, and benign tumors were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0
1

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
1
6
0
1
Order By: Relevance
“…As the BGW oVers a separate course on psychological factors for patients with skin diseases, stress factors and stress management in the job, these aspects are not addressed in this skin protection course. This procedure is in accordance with a study demonstrating that eczema patients may show psychosomatic involvement and that dermatologists tend to underestimate and misjudge this aspect (Poot et al 2000). All medical records (e.g.…”
Section: Methodssupporting
confidence: 86%
“…As the BGW oVers a separate course on psychological factors for patients with skin diseases, stress factors and stress management in the job, these aspects are not addressed in this skin protection course. This procedure is in accordance with a study demonstrating that eczema patients may show psychosomatic involvement and that dermatologists tend to underestimate and misjudge this aspect (Poot et al 2000). All medical records (e.g.…”
Section: Methodssupporting
confidence: 86%
“…Research on the structure and dynamics of families with psychosomatic patients have clearly revealed that one of the most typical dysfunctional characteristics in these families is the tendency to avoid expressing conflicts and emotional tensions. We can then understand and verify how difficulty in verbalizing emotional experiences is not the consequence of a lack of imagination and emotions, but results rather from the fact that emotions are carefully filtered so as to avoid tensions and conflict, and so as to conserve a pseudo‐harmony in the family system 33 . It should be noted, in addition, that not only the patient, but also all family members cooperate to achieve this aim.…”
Section: The Psychodermatological Patientmentioning
confidence: 99%
“…In een gerandomiseerde placebogecontroleerde studie werd het gunstig effect van het antidepressivum imipramine aangetoond (Perini et al, 1994 ). Er werden verder successen beschreven met inzichtgeorie¨nteerde psychotherapie (Koblenzer, 1995 ), met familietherapie (Poot et al, 2000 ) en met hypnose (Shenefelt, 2000 ). Harrison en Stepanek (1991) behandelden vijf patie¨nten met alopecia universalis en twee met uitgebreide alopecia areata met hypnosesessies.…”
Section: Inleidingunclassified